RETRACTED: Analysis the Effect of Profitability, Liquidity, Company Size and Business Risk on The Capital Structure of Companies Listed in the Jakarta Islamic Index (JII) PERIOD 2015-2017 - Olivia Monalisa Perez; Elwisam Elwisam; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the effect of profitability (return on assets), liquidity (current ratio), company size and business risk on capital structure in companies listed in the Jakarta Islamic Index (JII) for the period 2015-2017. The samples in this study were 16 companies that met the research criteria through non probability sampling method - purposive sampling. The analysis method used in this research is multiple linear analysis method processed with eviews 9 software. The results of this study indicate that profitability and liquidity have a negative and significant effect on capital structure, while company size and business risk have a positive and significant effect on capital structure.